THE CONCEPT OF MANAGEMENT OF INNOVATIVE DEVELOPMENT OF ENERGY SERVICE ENTERPRISES (INNOVATIVE ECONOMY, 2020)
Barna S.S. THE CONCEPT OF MANAGEMENT OF INNOVATIVE DEVELOPMENT OF ENERGY SERVICE ENTERPRISESPurpose. The aim of the article is to substantiate the concept of management of innovative development of energy service enterprises in Ukraine.Methodology of research. General and special methods are used in the course of the research, in particular methods: dialectics and scientific abstraction – in determining the essence of the concept of management of innovative development of energy service enterprises and its components; graphic – to depict the constituent elements of the concept in the relationship; monographic – to describe the concept, its ideas and provisions.Findings. The essence of the concept of management of innovative development of energy service enterprises as the generalized understanding of separate processes which comprehensively characterizes it and promotes achievement of the purposes or the decision of problems is defined. The constituent concepts are established, in particular: the purpose, principles and features of activity, and also functions, methods and tools by means of which the set purposes are reached. Emphasis is placed on the dependence of the management of innovative development of the enterprise on environmental factors that directly and indirectly determine the supply and demand for innovation in the field of energy services.A schematic representation of the concept is given. The essence and significance of each constituent element of the concept are detailed; the elements of the innovation management system are emphasized separately. The directions and tools of integration of innovative development into all subsystems of the enterprise are substantiated.The urgency of increasing the level of innovative development of energy service enterprises through the introduction of the latest developments is substantiated. Some innovative solutions to which energy service enterprises should pay attention are characterized.Originality. The understanding of the concept of management of innovative development of energy service enterprises is systematized, and also elements of external environment and system of management of innovative development are structured in detail. In contrast to existing developments, the proposed concept more clearly and comprehensively substantiates the theoretical foundations of integration of innovative development into all management subsystems, as well as systematizes the impact of external factors on the innovative development of energy enterprises.Practical value. The proposed concept forms a theoretical and methodological basis for improving the management system of innovative development of energy service enterprises and ensuring the growth of the level of innovative services to improve energy efficiency.Key words: energy service, energy efficiency, innovative development, innovative developments, innovations, concept, development, management.
Keywords: Key words; energy service; energy efficiency; innovative development; innovative developments; innovations; concept; development; management.